2013
DOI: 10.1002/jmri.24316
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of diffusion-weighted MR imaging in detecting acute appendicitis in children: Comparison with conventional MRI and surgical findings

Abstract: The use of combination of DWI and conventional MRI is a valuable technique in the diagnosis of acute appendicitis in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 20 publications
0
27
0
2
Order By: Relevance
“…With the diagnostic boundary set at ≥ 6mm, Bayraktutan et al 25 and Johnson et al 27 reported sensitivities of 92% 25 and 100% 27 and specificities of 100% 25 and 99% 27 respectively. With the diagnostic boundary set at ≥ 7mm, Rosines et al 30 and Herliczek et al 26 reported sensitivities of 94% 30 and 100% 26 and specificities of 100% 30 , 96% 26 respectively.…”
Section: Discussionmentioning
confidence: 99%
“…With the diagnostic boundary set at ≥ 6mm, Bayraktutan et al 25 and Johnson et al 27 reported sensitivities of 92% 25 and 100% 27 and specificities of 100% 25 and 99% 27 respectively. With the diagnostic boundary set at ≥ 7mm, Rosines et al 30 and Herliczek et al 26 reported sensitivities of 94% 30 and 100% 26 and specificities of 100% 30 , 96% 26 respectively.…”
Section: Discussionmentioning
confidence: 99%
“…No cases were classified as having indeterminate results in two studies . MRI findings were only classified into two categories (ie, positive vs. negative) in three studies . One study did not clearly explain how indeterminate cases were handled .…”
Section: Resultsmentioning
confidence: 99%
“…However, those authors did not include DWI in their MRI protocol, which has proven valuable in other abdominal and bowel diseases [19]. Bayraktutan et al [20] compared DWI with conventional unenhanced MRI and found that the combination of all sequences led to best sensitivity (92%) when evaluating for acute appendicitis. Our study is the first to compare unenhanced MRI versus contrast-enhanced MRI for the detection of appendicitis in pediatric patients, including the use of DWI.…”
Section: Discussionmentioning
confidence: 99%